The Link Between Financial Knowledge, Financial Product Awareness and Utilization: A Study among Small and Medium Enterprises in Zimbabwe - Mashizha, Margaret; Sibanda, Mabutho (International Journal of Economics and Financial Issues, 2017)
This paper reports on the findings from a survey which was conducted examine the level of utilization of financial products by SMEs and its linkage with financial knowledge among SMEs in Zimbabwe. The study was conducted following a realization that a significant number of SMEs were financially excluded despite efforts by the financial services sector to tailor make products to their needs. A quantitative research method was used where data was collected among a randomly selected sample of 400 SMEs in the capital city Harare, using a self-administered questionnaire. Findings indicated a lack of awareness of most financial product and hence low usage of these products by SMEs. An association between financial product awareness and financial knowledge was noted but no relationship between financial product usage and financial knowledge. The study concluded that although SMEs are financially knowledgeable, there is no link with their participation in the main financial stream. The study therefore recommended the need to further increase awareness at the same time encouraging participation in the financial markets to reduce vulnerability associated with financial exclusion. Keywords: financial knowledge, financial product awareness, financial product utilization, SMEs, Zimbabwe. JEL Classifications: D8, G1